Corporate actors: Definition, genesis, and interaction - Helena Flam (Max-Planck-Institut für Gesellschaftsforschung, 1990)
This paper focuses on the genesis of corporate actors - an upward transfer of decision-making rights and control functions within member-created organizations. It argues that the formation of oligarchies and oligarchic corporatization - as envisaged by Robert Michels - are both far more problematic than it is usually assumed, while member-activated corporatization is an often encountered phenomenon, which, however, does not exhaust all the possible routes to corporatization. Among those the paper singles out corporatization achieved through cross-system coalitions for closer inspection. The final section shows how different corporate structures, once in place, shape intercorporate interactions and thwart organizational goal-realization, thus spurring on further corporatization. – – Dieses Diskussionspapier betrachtet die Entstehung korporativer Akteure im Sinne des Transfers von Entscheidungs- und Kontrollfunktionen innerhalb von Mitgliederorganisationen. Es argumentiert, daß die Bildung von Oligarchien und oligarchischer Korporatisierung - wie von Robert Michels postuliert - weit problematischer sind als generell angenommen. Dagegen ist mitliederaktivierte Korporatisierung ein häufig zu beobachtendes Phänomen, wenngleich damit nicht alle möglichen Wege der Korporatisierung ausgeschöpft sind. Von diesen konzentriert sich das Papier auf Korporatisierung durch intersystemische Koalitionen. Im letzten Teil wird gezeigt, wie unterschiedliche korporative Strukturen interkorporative Interaktionen strukturieren und organisatorische Zielverwirklichung vereiteln, was schließlich weitere Korporatisierung provoziert.
Keywords: 300